Mycorrhizal fungi and plant diversity in tropical mountain rainforest of southern Ecuador - Suarez Chacon, J. (2017)
Mycorrhizal fungi, because of their obligate symbiotic interaction with plant roots, may either promote or restrict plant diversity depending on broad or narrow plant-fungus relationships. Inventories based on morphotyping and DNA sequencing were carried out on the mycorrhizal fungi associated with 115 species of trees (40 families), 20 of ericads and 4 of epiphytic orchids in a tropical mountain rainforest area of about twelve ha in southern Ecuador. Results indicated that diverse Glomeromycota with broad host ranges may promote high tree diversity while diverse but plant-family restricted Sebacinales likely support closely related Andean ericads. Similarly, distinct Tulasnellales and Sebacinales are associated with closely related species of epiphytic orchids. Ectomycorrhizal fungi were specifically associated with three Nyctaginacean trees and with one member of Melas-tomataceae. We conclude that the extraordinary high plant diversity of the tropical Andean forest is predominantly promoted by a broad range of mycorrhizal fungi but selected trees are supported by specific fungi.